Lilium candidum Extract Loaded in Alginate Hydrogel Beads for Chronic Wound Healing - Ioana Bâldea; Maria-Loredana Soran; Adina Stegarescu; Ocsana Opriș; Irina Kacso; Septimiu Tripon; Alexandra Adascalitei; Iulian George Fericel; Roxana Decea; Ildiko Lung (Gels)
Chronic wounds are a major health problem, affecting millions of people worldwide. Resistance to treatment is frequently observed, requiring an extension of the wound healing time, and improper care can lead to more problems in patients. Smart wound dressings that provide a controlled drug release can significantly improve the healing process. In this paper, alginate beads with white lily leaf extract were prepared and tested for chronic wound healing. The obtained beads were characterized by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Also, the efficiency of extract encapsulation in alginate was determined as being of. The obtained hydrogel was tested on two normal human cell lines, respectively, dermal fibroblasts (BJ-CRL-2522-ATCC) and endothelial cells (human umbilical vein endothelial cells—HUVEC 2). The longer release of bioactive compounds from plant extract loaded in the alginate hydrogel resulted in more effective wound closure, compared to the extract alone, and scar formation, compared to the alginate hydrogel. Therefore, the effect of the white lily extract in combination with that of sodium alginate hydrogel improves the biological activity of the alginate hydrogel and increases the wound healing properties of the alginate.